CENTRAL BLOOD PRESSURE ESTIMATION IN TYPE 1 DIABETES: IMPACT OF PERIPHERAL BLOOD PRESSURE CALIBRATION APPROACH. (June 2022) - Helleputte, Simon; Spronck, Bart; Sharman, James; Bortel, Luc Van; Segers, Patrick; Calders, Patrick; Lapauw, Bruno; de Backer, Tine
Abstract : Objective: Pulse wave analysis (PWA) of peripheral arterial pressure waveforms is used for non-invasive estimation of central blood pressure (BP), which can assist in cardiovascular (CV) risk assessment in populations with a high CV burden such as patients with type 1 diabetes (T1DM). However, correct calibration of peripheral BP waveforms is important in order to accurately estimate central BP. The impact of peripheral BP waveform calibration on central BP is not investigated yet in T1DM. Therefore, this study aims first for the first time in a T1DM patient cohort, to examine differences in central BP parameters estimated by PWA of radial BP waveforms, depending on which brachial BP (SBP/DBP vs. DBP/MAP) is used for calibration of the radial BP waveforms. Design and method: Cross-sectional study, in which adult T1DM patients without known CVD were enrolled. Radial artery BP waveforms were acquired using applanation tonometry (SphygmoCorâ) for the estimation of central systolic BP (central SBP), central pulse pressure (central PP) and central augmentation pressure (central AP), using either brachial SBP/DBP or DBP/MAP for calibration of the radial pressure waveforms. Brachial MAP was calculated using a fixed form factor of 40% (MAP = brachial DBP + 0.40 × brachial PP). Results: 54 patients (M/F: 32/22; age: 46 ± 9.5 yrs; T1DM duration: 27 ± 8.8 yrs) were evaluated. All three estimated central BP parameters were significantly higher when brachial DBP/MAP was used compared to SBP/DBP calibration (7.5 ± 5.04 mmHg, 7.5 ± 5.04 mmHg and 1.5 ± 1.36 mmHg higher central SBP, PP and AP, respectively, p < 0.001). Brachial-to-radial SBP amplification was estimated at 10 ± 7.1 mmHg (p < 0.001). Conclusions: This study confirms for the first time that in patients with T1DM there are significant differences in central BP parameters estimated with PWA, depending on the method used for calibration of the radial pressure waveforms. Brachial DBP/MAP calibration resulted in consistently higher central BP parameters as compared to using SBP/DBP. Hence, it seems that brachial-to-radial SBP amplification is important to take into account in the estimation of central BP parameters also in patients with T1DM.